Evaluation of Furniture Designs in Science Fiction Movies; Star Wars Example - Ardatürk, Ahmet Sadi (Street Art & Urban Creativity, 2023)
Both the phenomena of watching and being watched and furniture design are as old as human history. Today, it can be easily stated that the most fundamental provider of the phenomena of watching and being watched is the field of cinema, and the most major form of the relationship established with the visual is the art of cinema. Furniture, on the other hand, appears as a basic equipment used in the field of cinema. In this context, it can be stated that furniture, as a basic equipment used in cinematic works, is a part of the integrity of cinema and is one of the paradigms that constitute this integrity. Similar to many design fields such as editing, make-up, character in the art of cinema, it can be stated that furniture design (especially affecting the design and service of the stage) is a situation that can establish a direct connection with the user. The issue of furniture design in the art of cinema is taken very seriously by many directors. This study includes a research that evaluates, analyzes and interprets the furniture designs that exist in the art of cinema through the science fiction genre. The main films of the world-famous Star Wars universe were selected as the sample. The main reason for this selection is that, although the furniture related to the depiction of the reality existing in period cinemas contains a known design core, the furniture relationship in futurist works is a new design element. At this point, the relationship between furniture and the Star Wars universe, in which hundreds of works have been produced within a futurist scenario, has been questioned. A joint research has been carried out in the context of both design history, aesthetic knowledge and futurism with semantic, semiotic, functional and ergonomic analyzes. The general structure of the study is formed by discussing both the discourses of the furniture in the works and their functional, ergonomic and semiotic meanings. The study, which exists at the intersection of cinema and furniture design, reveals the relationship between the work-scenario-furniture by measuring the suitability of furniture designs in the context of futurism. As a result, design nuclei that will create a critical attitude towards the related works have been discovered.